The legal basis for international cooperation in suppressing the crime of financing terrorism - عبيد, اثير حسن; عباس, سرمد عامر (Journal of Legal Sciences, 2021)
The international society  feels the need to  the  placement of  means and  legal measures  and procedures  to fight the terrorism- financing crime   ,  thus  the UN  has issued  the international convention to fight  the financing of terrorism  for the year 1999 and a number of resolutions  undertaking to control  the terrorism funders  in the world,  specially the resolution  1373 for the year  2001  and followed by a number of states . The countries    have placed  legislations  suited with  the conditions of every state,  but all of these countries  agree  to confront  the judicial  and  security   legislations  for funding  the  terrorist  operations،   their efforts  are not fulfilled unless  by the support of the international  cooperation  for  fighting  these crimes